Advanced intelligent computing theories and applications. 11th International Conference, ICIC 2015, Fuzhou, China, August 20-23, 2015. Proceedings /: 11th International Conference, ICIC 2015, Fuzhou, China, August 20-23, 2015. Proceedings. Part III : (2015) - Unknown
No abstract available